The Influence of Organisational Culture on Firm Financial Performance : Case: S Group - Peltonen, Emma (My University, 2022)
The purpose of this thesis is to examine how does a subculture of a corporate group influ-ence the financial performance of a firm. As part of the formulation of the research ques-tion of this thesis, it is emphasised that this thesis examines the subcultures of a corpo-rate group, which are comparable to organisational culture in terms of scope of influence and thus significance. Consequently, this thesis aims to increase awareness of the link be-tween culture and financial performance on a general level. This study was executed as a commission to the Finnish S Group. The theoretical part of this thesis delves into the previous literature on subcultures and organisational culture in general, the relationship between organisational culture and leadership styles, presents the theoretical framework of this thesis, and justifies the study of the topic from a financial perspective. Accordingly the nine hypotheses of this thesis were formulated. In the empirical part of this thesis, in order to increase the understanding of the relationship between the intangible and tangible variables, both quantitative and qualitative research methods were used. The quantitative research method was a linear regression analysis which examined the relationship between cultural traits and combinations of traits on financial performance ratios. The ratios used in this thesis were turnover growth percentage, operating profit percentage, sales margin percentage and return on equity percentage. As a qualitative research method, a semi-structured interview method was used for this thesis by interviewing the chief executive directors of the target firms of this thesis and other leaders of S Group who were identified as having extensive knowledge of the topic. The purpose of the qualitative part of this thesis was to support and complement the findings from the quantitative part of this thesis and thus by the use of the qualitative research method, the aim of this thesis was to increase the understanding of the cause and effect relationship between organisational culture and firm financial performance. Based on the results of the quantitative part of this thesis, the organisational culture trait mission, the combinations of two traits mission and consistency, and mission and adaptability, and the combinations of three traits, where mission was one of the three traits, are connected and thus influence the firm financial performance, more specifically the operating profit percentage. No statistically significant results were obtained in the model explaining the turnover percentage, the sales margin percentage and the return on equity percentage with the explanatory variables. The results of the qualitative part of the thesis increased the understanding that the organisational culture trait influences financial performance only when the entire trait is of importance in terms of financial performance, rather than one or two indices of the trait. In addition, the qualitative part of this thesis increased the understanding of the underlying determinants for why certain cultural traits have a positive influence on the firm financial performance.

Tämän tutkielman tarkoitus on tutkia, miten yritysryhmän alakulttuuri vaikuttaa yrityksen taloudelliseen suorituskykyyn. Tutkielman tutkimuskysymyksen yhteydessä korostetaan, että tutkielmassa tarkastellaan yritysryhmän alakulttuureja, jotka ovat vaikutusalaltaan ja siten merkitykseltään verrattavissa organisaatiokulttuuriin. Tämän vuoksi tämän tutkielman tavoitteena on myös yleisellä tasolla lisätä ymmärrystä kulttuurin ja taloudellisen suori-tuskyvyn välisestä yhteydestä. Tutkielma toteutettiin toimeksiantona Suomessa toimivalle S-Ryhmälle. Tämän tutkielman teoriaosuudessa syvennytään sekä alakulttuureja että organisaati-okulttuuria yleisesti käsittelevään aiempaan kirjallisuuteen. Lisäksi teoriaosuudessa tar-kastellaan organisaatiokulttuurin ja johtamistyylien välistä yhteyttä sekä esitellään tämän tutkielman teoreettinen viitekehys ja perustellaan aiheen tutkiminen rahoituksen näkökulmasta. Tutkielman yhdeksän hypoteesia on muotoiltu tämän tutikelman te-oreettisen viitekehyksen mukaisesti. Tutkielman empiirisessä osuudessa käytettiin sekä kvantitatiivista että kvalitatiivista tutki-musmenetelmää organisaatiokulttuurin ja taloudellisen suorituskyvyn välisen suhteen ymmärryksen lisäämiseksi. Tutkielman ensisijainen tutkimusmenetelmä oli kvantitatiivinen tutkimusmenetelmä, lineaarinen regressioanalyysi, jonka avulla tutkittiin kulttuurin ominaisuuksien sekä ominaisuuksien kombinaatioiden välistä suhdetta taloudellisiin tun-nuslukuihin, jotka olivat liikevaihdon kasvuprosentti, liikevoittoprosentti, myyn-tikateprosentti ja oman pääoman tuottoprosentti. Kvalitatiivisena tutkimusmenetelmänä tutkielmassa käytettiin puolistrukturoitua haastattelumenetelmää, jossa haastateltiin tutkielman kohdeyritysten johtajia, joilla todettiin olevan laajaa tietoa tutkittavasta ai-heesta. Kvalitatiivisen osuuden tarkoituksena oli tukea ja täydentää kvantitatiivisesta osuudesta saatuja tuloksia, ja siten lisätä ymmärrystä organisaatiokulttuurin ja yrityksen taloudellisen suorituskyvyn välisestä syy-seuraussuhteesta. Tutkielman kvantitatiivisen osuuden tulosten perusteella organisaatiokulttuurin ominaisuus missio, kahden ominaisuuden kombinaatiot missio ja johdonmukaisuus, sekä missio ja sopeutumiskyky, sekä kolmen ominaisuuden kombinaatiot, joissa missio oli yksi kolmesta ominaisuudesta, ovat yhteydessä ja vaikuttavat yrityksen taloudelliseen suori-tuskykyyn, liikevoittoprosenttiin. Malleilla, joilla tutkittiin liikevaihdon kasvuprosentin, myyntikateprosentin ja oman pääoman tuottoprosentin yhteyttä selittäviin muuttujiin, ei saatu tilastollisesti merkitseviä tuloksia. Kvalitatiivisen osuuden tulokset lisäsivät ymmär-rystä siitä, että organisaatiokulttuurin ominaisuus vaikuttaa taloudelliseen suorituskykyyn vain silloin, kun koko ominaisuudella on merkitystä taloudellisen suorituskyvyn kannalta, eikä ainoastaan yhden tai kahden ominaisuuden indeksillä. Lisäksi tämän tutkielman kvalitatiivinen osuus lisäsi ymmärrystä siitä, miksi tietyt kulttuuriset ominaisuudet vaikuttavat myönteisesti yrityksen taloudelliseen suorituskykyyn.
Keywords: rahoitus; organisaatiokulttuuri; regressioanalyysi; suorituskyky; analyysi; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance